MiR-20b Displays Tumor-Suppressor Functions in Papillary Thyroid Carcinoma by Regulating the MAPK/ERK Signaling Pathway - Hong, Shubin; Yu, Shuang; Li, Jin; Yin, Yali; Liu, Yujie; Zhang, Quan; Guan, Hongyu; Li, Yanbing; Xiao, Haipeng (Thyroid (New York, N.Y.), 2016)
MicroRNAs (miRNAs) are endogenous, small, non-coding RNAs that play important roles in multiple biological processes. MiR-20b has been reported to be dysregulated in papillary thyroid carcinoma (PTC). However, the functional roles are still largely unknown. This study aimed to investigate the biological functions and the underlying molecular mechanisms of miR-20b in PTC. The expression of miR-20b was assessed by quantitative reverse transcription polymerase chain reaction in 47 pairs of PTC and adjacent normal thyroid tissues. The association between miR-20b expression and clinicopathologic status of PTC patients was analyzed. MiR-20b was overexpressed in the PTC cell lines K1 and TPC-1, and the effects on cell viability, migration, and invasion were evaluated. The study further searched for targets of miR-20b, and identified the possible molecular mechanisms of miR-20b in PTC cells. Additionally, the effect of miR-20b on tumor growth in nude mice was assessed. It was found that miR-20b was markedly downregulated in PTC tissues compared with their adjacent normal thyroid tissues. The low-level expression of miR-20b was correlated with cervical lymph node metastasis and TNM staging. Upregulation of miR-20b inhibited cell viability, migration, and invasion in K1 and TPC-1 cells. Ectopic overexpression of miR-20b could suppress the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling pathway through directly targeting son of sevenless homolog 1 (SOS1) and extracellular signal-regulated kinase 2 (ERK2). Furthermore, depletion of SOS1 or ERK2 by siRNAs has similar effects as miR-20b overexpression on cell viability and invasion, whereas rescued SOS1 or ERK2 expression partially reversed the inhibitory effects of miR-20b in TPC cell lines. In xenograft animal experiments, it was found that overexpressed miR-20b could suppress tumor growth of PTC cells. These results indicate for the first time that miR-20b displays tumor-suppressor functions in PTC. By targeting SOS1 and ERK2, miR-20b inhibits the activity of the MAPK/ERK signaling pathway. The findings suggest that miR-20b may play an important role in PTC initiation, progression, and metastasis, and may provide a potential therapeutic target for PTC.